Glutamic Acid Transporters: Targets for Neuroprotective Therapies in Parkinson’s Disease - Li, Xiang; Wang, Wenjun; Yan, Jianghong; Zeng, Fancai (Frontiers in Neuroscience, 2021)
Parkinson's disease (PD) is a common neurodegenerative disease in middle-aged and elderly individuals. At present, no effective drug has been developed to treat Parkinson's disease. Although a variety of drugs exist for the symptomatic treatment of Parkinson's disease, they all have strong side effects. Most studies on Parkinson's disease mainly focus on dopaminergic neurons. This review highlights the function of glutamic acid transporters (GLTs), including excitatory amino acid transporters (EAATs) and vesicular glutamate transporters (VGLUTs), during the development of PD. In addition, using bioinformatics, we compared the expression of different types of glutamate transporters genes in the cingulate gyrus of Parkinson's disease patients and healthy controls. More importantly, we suggest that the functional roles of glutamate transporters may prove beneficial in the treatment of PD. In summary, VGLUTs and EAATs may be potential targets in the treatment of PD. VGLUTs and EAATs can be used as clinical drug targets to achieve better efficacy. Through this review article, we hope to enable future researchers to improve the condition of PD patients.